2010
DOI: 10.1111/j.1442-2050.2010.01135.x
|View full text |Cite
|
Sign up to set email alerts
|

The expression of CXCR4 and its relationship with matrix metalloproteinase-9/vascular endothelial growth factor in esophageal squamous cell cancer

Abstract: Esophageal cancer (EC) is a highly aggressive neoplasm with poor prognosis. The main reason for this disappointing outcome is the strong behavior of esophageal cancer cell's invasion and metastasis. CXC chemokine receptor 4 (CXCR4) was found to be expressed in many tumors and significantly correlated with invasion, angiogenesis, metastasis, and prognosis. In the present study, we investigated the expressions of CXCR4, matrix metalloproteinase-9 (MMP-9), and vascular endothelial growth factor (VEGF) in esophage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 22 publications
3
32
1
Order By: Relevance
“…The CXC chemokine ligand 12/CXCR4 signaling pathway plays an important role in carcinogenesis, progression, and metastasis, which results in decreased overall survival (OS) and poor prognosis. [13][14][15] Although the concomitant expression of CD133-CXCR4 and their prognostic role in prostate, pancreatic, colon, and renal cancers have been demonstrated, [16][17][18][19] no related studies have been performed in ESCC. Our previous studies have proved that CXCR4 expression is significantly associated with prognosis in ESCC, as well as matrix metalloproteinase-9/vascular endothelial growth factor expression.…”
Section: Perspectivementioning
confidence: 98%
“…The CXC chemokine ligand 12/CXCR4 signaling pathway plays an important role in carcinogenesis, progression, and metastasis, which results in decreased overall survival (OS) and poor prognosis. [13][14][15] Although the concomitant expression of CD133-CXCR4 and their prognostic role in prostate, pancreatic, colon, and renal cancers have been demonstrated, [16][17][18][19] no related studies have been performed in ESCC. Our previous studies have proved that CXCR4 expression is significantly associated with prognosis in ESCC, as well as matrix metalloproteinase-9/vascular endothelial growth factor expression.…”
Section: Perspectivementioning
confidence: 98%
“…Moreover, the authors confirmed that the intervention therapy targeting the CXCL12/CXCR4 axis may open a new direction for ESCC patients' treatment [45,46]. The significant correlation between CXCR4 expression and clinicopathological features of EC was also proved by Lu et al, who indicated that the immunoreactivity of this receptor was significantly associated with tumor grade, size, depth of tumor invasion, presence of lymph node metastases, or tumor stage (TNM), suggesting that CXCR4 plays an important role in EC progression [47]. The expression of CXCL12 and CXCR4 at the mRNA and protein level was confirmed by reverse transcription polymerase chain reaction (RT-PCR) and Western blot in human ESCC cell line EC9706 [48].…”
Section: Chemokines and Their Receptors-the Role In Esophageal Cancermentioning
confidence: 92%
“…Moreover, IL-8 concentrations correlated with proinflammatory cells and biochemical marker of inflammation-C-reactive protein. However, the authors concluded that detection rates were not satisfactory enough to allow for the recommendation of IL-8 determination as an adjunct to the clinical evaluation of lymph node involvement in ESCC •CXCR4 expression correlated with tumor grade and size, depth of tumor invasion, presence of lymph node metastases, and tumor stage (TNM) [47] 3 CXCL8/CXCR-2 Expression •CXCL-8/CXCR-2 coexpression correlated with depth of invasion, lymph node metastasis, pathologic stage, and lymphatic and venous invasion [50] •CXCL-8 expression was independent predictive factor for recurrence-free ESCC patients' survival 6 CXCR2 Expression •CXCR2 expression correlated with lymph node metastasis and was an independent prognostic factor for survival of patients with resected ESCC [51] 7 CCR7 Expression •CCR7 expression correlated with lymph node metastasis, histological grade, lymphatic and vessel invasions, and tumor stage [52,53] •CCR7 expression was independent prognostic factor for EC patients' survival [53] …”
Section: Chemokines and Their Receptors-the Role In Esophageal Cancermentioning
confidence: 98%
See 1 more Smart Citation
“…In breast cancer, CAFs produce the chemokine CXCL12/SDF-1, that can recruit endothelial progenitor cells into the tumor mass thus promoting angiogenesis; SDF-1 can directly stimulate the CXCR4 cognate receptor expressed on breast carcinoma cells promoting lymph nodal metastasis (Orimo & Weinberg 2006). Interestingly, CXCR4 has been identified as a transcriptional target of wild-type RET (Lu et al 2011). Furthermore, CXCR4 mRNA could be induced by both PTC-associated RET mutants (RET/PTC1 and RET/PTC3) in follicular thyroid epithelial cells (Castellone et al 2004 and by MTC-associated RET mutants (RET MEN2B).…”
Section: Desmoplastic Stromamentioning
confidence: 99%